Reseña de Torres Sánchez, M. Á. (2000), La interjección, Cádiz, Servicio de Publicaciones de la Universidad de Cádiz. - Jacinto Espinosa García (Pragmalingüística)
Se trata de reseña de Torres Sánchez, M. Á. (2000), La interjección, Cádiz, Servicio de Publicaciones de la Universidad de Cádiz.